Utilization of Fixed Dome Reactor for Biogas Production from Cow Manure: Supporting Green Economy in Labuan Ratu Satu Village - Andri Sanjaya; Yunita Fahni; Nurul Mawaddah; Agriadi Dwi Nugroho Putro; Amedeo Cavendish; Anugrah Ayub Waskito; Arifino Decika Rachman; Muhammad Bagus Tri Jaya Saputra (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
One of the strategic steps in promoting a green economy is converting organic waste, particularly cow manure, into renewable energy in the form of biogas. The cow manure processing system utilizes a fixed dome technology. This fixed-dome features a dome-shaped construction of brick and concrete below the ground surface. Labuan Ratu Satu Village was selected as the site for implementing fixed dome reactor technology to convert cow manure into biogas. This activity aims to facilitate sustainable waste management and offer an eco-friendly alternative energy source. The method comprises an initial site survey, community engagement regarding the biogas concept, technical training, and the installation and operation of the reactor. The fixed dome reactor has been effectively installed and is operational, generating biogas for the local community's use. These accomplishments are anticipated to promote establishing a sustainable green economy at the village level, concurrently enhancing the community's quality of life through using renewable energy. This initiative is anticipated to serve as a paradigm for organic waste management in other regions.